Culeolus suhmi Herdman. According 1881 - Sanamyan, K. E.; Sanamyan, N. P. (Zenodo, 2002)
Culeolus suhmi Herdman, 1881 (®gure 28) Culeolus suhmi Herdman, 1881: 86; Monniot and Monniot, 1973: 453 (synonymy); 1974: 765; 1985a: 300; 1985b: 31; Millar, 1955: 232; 1959: 199 (part, not specimens from Kermadec Trench). Not Culeolus suhmi : Millar, 1970: 136 (5 C. anonymus ). Several specimens of this species were collected in the central Atlantic during cruise 40 of RV Academic Kurchatov we describe them for comparison with C. anonymus . Material examined . St. 4306, 3425 m, 09 ss 28.8 ¾ N, 54 ss 41.5 ¾ W, 24 November 1984, six specimens. Description . The body length is 3±6 cm, the peduncles in most specimens are broken, the longest is 28 cm in length. The test is thick, hard and rigid, covered by papillae of various lengths and by hydroids. A complete ring of long crowded papillae encircles the posterior end of the body with the small atrial aperture in the centre of this ring. There are a few separate and relatively long papillae on the midventral line, but they do not form a distinct mid-ventral crest. The internal structure was studied in one 6 cm specimen only, the others were too damaged. Body muscles form a regular network as in many other species of the genus, but this species also has a conspicuous bundle of thick longitudinal muscles just anterior to the dorsal tubercle. Twenty-one relatively short and poorly branched branchial tentacles have only primary and occasionally, secondary, branches. The branchial sac has six folds on each side, the branchial formula is: E5(10)6 (7)8(6)8(14)7(10)8(16)5DL7(13)13 (11)9 (12)9 (6)9(6)4(3)4E. Two gonads are present on the left and three on the right side. On the left, one gonad (consisting of ®ve lobes) is inside the gut loop and the other (consisting of seven lobes), is outside. Both are about as long as the descending limb of the gut loop and end more or less at the same level not far from the anus. On the right, the gonads are shorter, consisting of two or three lobes lying parallel to the endostyle. The presence of three gonads may be an abnormality, especially as they are in one line with the distal end of one being in contact with the proximal end of another, suggesting that one long gonad has divided into two. Two posterior gonads on the right end are close to each other. The anal border has two large, lobed lips, as in C. antarcticus . : Published as part of Sanamyan, K. E. & Sanamyan, N. P., 2002, Deep-water ascidians from the south-western Atlantic (RV Dmitry Mendeleev, cruise 43 and Academic Kurchatov, cruise 11), pp. 305-359 in Journal of Natural History 36 (3) on pages 350-351, DOI: 10.1080/00222930010004232, http://zenodo.org/record/5299679 : {"references": ["HERDMAN, W. A., 1881, Preliminary report on the Tunicata of the Challenger Expedition. Cynthiidae, Proceedings of the Royal Society, Edinburgh, 11 (3), 52 \u00b1 88.", "MONNIOT, C. and MONNIOT, F., 1973, Ascidies abyssales reAcolteAes au cours de la campagne oceAanographique BiacEores par le`Jean Charcot', Bulletin du MuseAum national d' Histoire naturelle, Paris, (3), 121 (Zool. 93), 389 \u00b1 475.", "MILLAR, R. H., 1955, Ascidiacea, Reports of the Swedish Deep-Sea Expedition, 2 (18), 223 \u00b1 236.", "MILLAR, R. H., 1959, Ascidiacea, Galathea Report, 1, 189 \u00b1 209.", "MILLAR, R. H., 1970, Ascidians, including specimens from the deep sea, collected by R. V.`Vema' and now in the American Museum of Natural History, Zoological Journal of the Linnean Society, 49, 99 \u00b1 159."]}